A study on eccentric occluder via ultra minimal incision of doubly committed subarterial ventricular septal defects. Issue 6 (11th March 2021) - Gao, Qiang; Jin, Jie; Zhang, Zewei; Ma, Lianglong; Li, Jianhua; Yu, Jiangen
Abstract: Object: To compare the clinical data of sternotomy and left intercostals incision, combined with the literature, to provide the best surgical incision for committed subarterial ventricular septal defect (DCS‐VSD). Methods: From July 2016 to July 2020, a total of 117 cases of occlusion surgeries for DCSVSD, which guided by transoesophagel echocardiography (TEE) were completed, including 34 cases with sternotomy incision and 83 cases with left intercostal incision. Statistics and analysis of the operation and follow‐up. Results: A total of 115 cases successfully occluded, the successful rate was 98.29%, and 1 case failed in each group. Pericardial effusion occurred in five children after the drainage device was removed, and the pericardial effusion disappeared after diuretic treatment. There was no statistical difference between the two groups in operation time, occlusion time, thoracotomy time and postoperative hospital stay. All the children recovered and were discharged from the hospital, and were followed‐up for 2–30 months after operation. Conclusion: TEE‐guided intercostal DCS‐VSD occlusion is safe and effective. There is no statistical difference between two approach with the operation time, chest opening and closing time, occluder placing time, and postoperative hospital staying. At the same time, the surgical incision by intercostal incisionis smaller and the operation invasion is less, it is a surgical approach which worth to develop.